Nilai-Nilai Pendidikan Islam dalam Aqiqah - Mualimin, Mualimin (Universitas Islam Negeri Raden Intan Lampung, 2015)
Islam is a perfect religion that covers all aspects of life in life, a Muslim is required to hold the two matters which mentioned to the prophet in a hadith, al Qur'an and al-Hadith. In both the Islamic sources have listed all of the laws that manage of life. Hadiths are the words, deeds, and what will be implemented by the prophet Muhammad saw is used as a second source of Islamic law. But the hadith is not just talking about law and worship, but also a broader discussion of it. For example, talking about faith, cultural, social, ways of life, morals, etc.One example of the sunnah or hadith that talking about social problems is hadith about faith through this worship, prophet Muhammad saw convey messages and values that must be implemented his followers. In this paper, the authors about having faith in the religion of Islam, furthermore, implemented and analyzed the hadith, and at the conclusion to explain about faith and valves of any education contained in worshiping faith in Islam.